Embodied playwriting : improv and acting exercises for writing and devising - Bucs, Hillary Haft; Menefee, Charissa (New York, NY : Routledge, 2023)
"Embodied Playwriting: Improv and Acting Exercises for Writing and Devising is the first book to compile new and adapted exercises for teaching playwriting in the classroom, workshop, or studio through the lens of acting and improvisation. The book provides access to the innovative practices developed by seasoned playwriting teachers from around the world who are also actors, improv performers, and theatre directors. Borrowing from the embodied art of acting and the inventive practice of improvisation, the exercises in this book will engage readers in performance-based methods that lead to the creation of fully imagined characters, dynamic relationships, and vivid drama. Step-by-step guidelines for exercises, as well as application and coaching advice, will support successful lesson planning and classroom implementation for playwriting students at all levels, as well as individual study. Readers will also benefit from curation by editors who have experience with high-impact educational practices and are advocates for the use of varied teaching strategies to increase accessibility, inclusion, skill-building, and student success. Embodied Playwriting offers a wealth of material for teachers and students of playwriting courses, as well as playwrights who look forward to experimenting with dynamic, embodied writing practices"--
Embodied playwriting / Hillary Haft Bucs and Charissa Menefee -- The meet and greet : creating opportunities for surprise and discovery / Charissa Menefee -- Improvising between the lines : enhancing the script by embodying subtext / Amy Seham -- Using improv to create original plays : respectfully writing diverse characters / Stephanie Rae -- Character's search for authenticity : improvisation for the revision process / Muneeb ur Rehman -- The picture project : originating story through movement / Sarah Kozinn -- Physical expressions in devised playwriting / Luane Davis Haggerty and Aaron Kelstone -- Active group playwriting : psychodramatic techniques adapted for playmaking / David Kaye -- Building the world of the play through collaborative performance / Mike Poblete -- It's all about play : locating the game in embodied playwriting / John P. Bray -- Folkgames as creative stimulus for devising : the case of Chaskele / Solomon Y. Dartey -- 'Laughter that shatters' : improv techniques for social justice comedy playwriting / Elspeth Tilley -- Writing for change : guiding activist playwrights in classrooms and communities / Dana Edell -- Community-based play creation / Hope McIntyre -- Writing climate justice : personal storytelling and source material devising as embodied methodology / Joan Lipkin and Kasey Lynch -- Embodied playwriting exercises for classroom, workshop, and studio : skill-building and content generation / edited and curated by Hillary Haft Bucs and Charissa Menefee -- Embodied playwriting exercises for classroom, workshop, and studio : the revision process / edited and curated by Hillary Haft Bucs and Charissa Menefee.
Keywords: Playwriting -- Study and teaching; Improvisation (Acting) -- Study and teaching; PERFORMING ARTS / Theater / Playwriting